2021
DOI: 10.1002/chem.202100263
|View full text |Cite
|
Sign up to set email alerts
|

Mapping C−H⋅⋅⋅M Interactions in Confined Spaces: (α‐ICyDMe)Au, Ag, Cu Complexes Reveal “Contra‐electrostatic H Bonds” Masquerading as Anagostic Interactions**

Abstract: What happens when a C−H bond is forced to interact with unpaired pairs of electrons at a positively charged metal? Such interactions can be considered as "contraelectrostatic" H-bonds, which combine the familiar orbital interaction pattern characteristic for the covalent contribution to the conventional H-bonding with an unusual contra-electrostatic component. While electrostatics is strongly stabilizing component in the conventional C−H×××X bonds where X is an electronegative main group element, it is destabi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 84 publications
2
19
0
Order By: Relevance
“…Very recent computational studies by Alabugin, Sollogoub and co‐workers demonstrated that these attractive interactions are also present in methane complexes with NHC‐Au‐Cl, thus emphasizing that Au⋅⋅⋅H−C hydrogen bonds are not exclusively the result of steric congestion. [24a] …”
Section: Resultsmentioning
confidence: 99%
“…Very recent computational studies by Alabugin, Sollogoub and co‐workers demonstrated that these attractive interactions are also present in methane complexes with NHC‐Au‐Cl, thus emphasizing that Au⋅⋅⋅H−C hydrogen bonds are not exclusively the result of steric congestion. [24a] …”
Section: Resultsmentioning
confidence: 99%
“…[28] In contrast to agostic interactions that are understood as three‐center‐two‐electron bonds between C−H and vacant d ‐orbitals of transition metals with rather short H−M distances and narrow C−H−M angles (≈1.8–2.3 Å; ≈90–140°), the weaker anagostic interactions are associated with filled d ‐orbitals, longer H−M distances and larger C−H−M angles (≈2.3–2.9 Å; ≈110–170°). [29] Consequently, M I (M=Cu, Ag, Au) complexes, that exclusively feature occupied d ‐orbitals, are good candidates to observe such contacts. The 29 Si NMR spectrum of 4 displays a single resonance at δ( 29 Si)=+67.6 ppm.…”
Section: Resultsmentioning
confidence: 99%
“…The later term emphasises the relation to classical H‐bonds, which however differ in the charge of the C and H atom upon approximation of the donor (gold versus the H‐bond acceptor). Very recent computational studies by Alabugin, Sollogoub and co‐workers demonstrated that these attractive interactions are also present in methane complexes with NHC‐Au‐Cl, thus emphasizing that Au⋅⋅⋅H−C hydrogen bonds are not exclusively the result of steric congestion [24a] …”
Section: Resultsmentioning
confidence: 99%